Raised CRP levels mark metabolic and functional impairment in advanced COPD. Issue 1 (29th July 2005) - Broekhuizen, R; Wouters, E F M; Creutzberg, E C; Schols, A M W J
Abstract : Background: C-reactive protein (CRP) is often used as a clinical marker of acute systemic inflammation. Since low grade inflammation is evident in chronic diseases such as chronic obstructive pulmonary disease (COPD), new methods have been developed to enhance the sensitivity of CRP assays in the lower range. A study was undertaken to investigate the discriminative value of high sensitivity CRP in COPD with respect to markers of local and systemic impairment, disability, and handicap. Methods: Plasma CRP levels, interleukin 6 (IL-6) levels, body composition, resting energy expenditure (REE), exercise capacity, health status, and lung function were determined in 102 patients with clinically stable COPD (GOLD stage II–IV). The cut off point for normal versus raised CRP levels was 4.21 mg/l. Results: CRP levels were raised in 48 of 102 patients. In these patients, IL-6 (p<0.001) and REE (adjusted for fat-free mass, p = 0.002) were higher while maximal (p = 0.040) and submaximal exercise capacity (p = 0.017) and 6 minute walking distance (p = 0.014) were lower. The SGRQ symptom score (p = 0.003) was lower in patients with raised CRP levels, as were post-bronchodilator FEV1 (p = 0.031) and reversibility (p = 0.001). Regression analysis also showed that, when adjusted for FEV1, age and sex, CRP was a significant predictor for body mass index (p = 0.044) and fat mass index (p = 0.016). Conclusions: High sensitivity CRP is a marker for impaired energy metabolism, functional capacity, and distress due to respiratory symptoms in COPD.